Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada PT. Inti Harum Sentosa Ruteng - Yulita Ndayung; Stefanus Hubertus Gusti Ma; Marsel Nande (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This study aims to determine whether financial compensation and non-financial compensation affect the performance of employees at PT. Inti Harum Sentosa Ruteng Manggarai Regency, East Nusa Tenggara Province (NTT). The type of research used is associative quantitative. The result of the study indicate that there is simultaneously the influence of financial and non-financial compensation variabels on employee performance at PT. Inti Harum Sentosa Ruteng. But partially the financial compensation variable does not affect the performance of employees while non-financial compensation affects the performance of empleyees of PT. Inti Harum Sentosa Ruteng.